Italy: Immigration and the evolution of populism - Luca Pieroni; Melcior Rosselló Roig; Luca Salmasi (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2021)
We estimate the impact of immigration on the upsurge of populism in Italy. Our data considers electoral results at municipality level of the Senate of the Italian Republic and the Chamber of Deputies over the period 2006-2018. Findings in our research point toward a positive impact of the share of migrants on the rise of right-wing populist parties. According to our estimates the size of the average increase of the share of immigrants between our first and last electoral years (3.33 percentage points) corresponds to an increase of 2.08 percentage points for the Centre-right coalition. Lega is the party that capitalizes the most out of the anti-immigration. The size of the effect for Lega raises to 6.41 percentage points. We explore the heterogenous effect of how the antiimmigration rhetoric is the main mechanism that exacerbates out of fear and insecurity the gap between Lega and its most direct rivals. Our paper offers a fresh view by looking at plausible mechanisms behind our results by inspecting the European Social Survey.
Keywords: P16; D72; J15; 330; Immigration; Populism; Italy; Instrumental Variables